The Means of Will Expression in the Poetry of Lesya Ukrainka (Linguostylistic Studies, 2014)
The article analyses the linguistic means of will expression used in the poetry of Lesya Ukrainka. It was found that the will expression is one of the major modalities in her poetry. Most often the prompting was conveyed by various forms of the imperative. Also there are elliptical sentences and indirect prompting structures, where the will expressions were marked by the grammatical means of addressed language and second person pronouns, combined with the corresponding lexical content. Another feature of the poetry of Lesya Ukrainka is the large number of grammatical patterns of self-prompting reflecting the struggle against the terminal illness which the poet carried throughout all her life. This is another indication of a main character of her poetry being a combination of the speaker, a recipient and a member of the audience. The paper also describes verbal means of will expression in the play «The Boyar’s Wife», where all priming structures are illustrations not only of poetic speech, but also of ordinary communicative situations that reinforce remarks describing the nonverbal behaviour of characters. Key words: will expression, sender, recipient, imperative, communicative situation. References